Aplikasi Perhitungan Biaya Instalasi Listrik Pada Bangunan Berbasis Android - Wafiah, Andi; Setiawan Jufri, Ronni (Jurnal Sintaks Logika, 2021)
Electric power has a very important role in everyday life. The rise of the construction of new houses or buildings is accompanied by the increasing amount of electricity needed to meet these needs. Currently the development of technology is very rapid, especially Android smartphones. Therefore, to keep up with the development of science and technology that is increasingly rapidly in this era, an application is designed that can calculate the cost of electrical installations.Design Android applications are built using the Javascript and Dart programming languages​which are built using the Flutter Framework and use the Firebase database.The android application design is tested using Black Box testing which states that the system is running as needed and free from errors.Keywords : Installation, Electrical, Flutter, Visual Studio Code, Android.